Transforming herbal medicines: Integrating traditional knowledge with modern pharmaceutical advancements - G. Patel, Madhavi; A. Shah, Priya; G. Prajapati, Bhupendra; Sriamornsak, Pornsak (Science, Engineering and Health Studies, 2025)
Herbal medicines have been known for centuries for healing and maintaining human health; according to the WHO, over 80% of the world’s population relies on them for primary healthcare. Different countries and cultures have their own traditional medicine systems that utilize natural products, and humans have utilized that vast reservoir of knowledge for the benefit of society. Over time, the availability of standardized conventional medicines has decreased interest in herbal medicines. However, following the emergence of life-threatening viral diseases, interest in herbal medicines has resurged, leading to their increased use as remedies or for preventive purposes. However, the inconsistent quality, arising from issues such as authenticity, geographical origin, species variation, and a lack of quality control, has cast doubt on the efficacy of these natural treatments. Currently, advancements in sophisticated techniques for establishing herbal standards, including modern extraction technologies such as supercritical fluid, ultrasound-assisted and microwave-assisted extraction; analytical tools like HPLC-MS, spectroscopy, and DNA barcoding; and in silico approaches such as computational drug screening and network pharmacology, have renewed interest in herbal medicines. Historically, herbal medicines were prepared in traditional dosage forms, which have evolved into standardized preparations through scientific advancement. Modernizing the field through the development of nano-formulation, the enhancement of extraction and analytical techniques, and the application of DNA fingerprinting, biotechnological screening, and computational methods is establishing pharmacological efficacy and standardization. These innovations provide the proof of concept needed to convert ancient knowledge into modern remedies. Various formulation approaches, representing pharmaceutical innovations in herbal medicines, have been found to increase bioavailability by up to 5-50 times and improve the stability of dosage forms, resulting in enhanced efficacy. Recognizing these advancements, many countries have begun to regulate herbal products similarly to conventional medicines, implementing standards such as good manufacturing practices. The herbal market is expected to reach $437 billion by 2032, and these developments, combined with regulatory improvements, are assisting herbal treatments in gaining international recognition. Although herbal products are generally regarded as safe, multidisciplinary studies are needed to validate their safety and efficacy. Establishing clinical efficacy through clinical trials should be a primary focus of future research. With these innovations, herbal medicine holds the potential to address many challenges associated with chronic and communicable diseases.